The impact of the recent regulatory changes regarding non-financial information in Spain on the corporate reporting quality, measured by the analysts forecast accuracy - Smith Burrull, Blanca (2020)
The purpose of this study is to examine whether the recent Spanish regulation on non-financial information has improved the quality of corporate reporting in the Spanish firms subject to this regulation. To this aim, this research investigates the impact of the Law 11/2018 on the analysts forecast accuracy. A higher quality in the non-financial information should provide more information about the future prospects of the companies, increasing the analysts forecast accuracy. Accordingly, this research tests the hypotheses that the Law 11/2018 has reduced either the analyst forecast error and analyst forecast dispersion, which are proxies for forecast accuracy. This research analyze a sample of 170 observations corresponding to 85 Spanish public listed companies trading during the years 2018 and 2019, before and after the forecasts could be formulated based on information complying with the Law 11/2018. A regression model has been created in order to test the hypothesis of an improvement in the forecast accuracy as a result of the enforcement of the Law 11/2018. The results show that there is no evidence to support the hypothesis that the enforcement of the Law 11/2018 has had a significant effect on improving the analyst forecast accuracy. Consequently, the conclusion of this research is that the quality of non-financial information has not improved significantly as a result of the Law 11/2018.